Dust Devils on Titan. Issue 3 (3rd March 2020) - Jackson, Brian; Lorenz, Ralph D.; Barnes, Jason W.; Szurgot, Michelle
Abstract: Conditions on Saturn's moon Titan suggest that dust devils, which are convective, dust‐laden plumes, may be active. Although the exact nature of dust on Titan is unclear, previous observations confirm an active aeolian cycle, and dust devils may play an important role in Titan's aeolian cycle, possibly contributing to regional transport of dust and even production of sand grains. The Dragonfly mission to Titan will document dust devil and convective vortex activity and thereby provide a new window into these features, and our analysis shows that associated winds are likely to be modest and pose no hazard to the mission. Plain Language Summary: Saturn's moon Titan may host active dust devils, small dust‐laden plumes, which could significantly contribute to transport of dust in that moon's atmosphere. Although the exact nature of dust on Titan is unclear, previous observations confirm that there is actively blowing dust on that world. If dust devils are active on Titan's surface, NASA's upcoming Dragonfly mission is likely to encounter them, but dust devils on Titan are unlikely to pose a hazard to the mission. Key Points: As probed by Huygens, the meteorological conditions near the surface of Saturn's moon Titan appear conducive to dust devil formation Dust devils may contribute significantly to Titan's aeolian cycle If dust devils are active on Titan, NASA's upcoming Dragonfly mission is likely to encounter them